Community structure of the secondary forest adjacent to the University Library, University of the Philippines Visayas, Miagao, Iloilo. - Sadio, Venus D. (2013.)
A one-hectare plot of secondary forest adjacent to the University Library was chosen as the study area. This is the first systematic study done so far in the area in accordance to the "Love Nature Park" project proposed by the University Administration. Consequently, the present study will provide some vital information needed for its proper management and maintenance. This study also aims to assess the community structure of trees in the area using accepted ecological indicators. Using the transect line plot method the structure of the tree community was studied with four quadrants established. The local name/scientific name of each tree in the plot was identified as well as its GBH and height. From the data gathered, community structure is described in terms of the following parameters: relative density, relative frequency, relative dominance, importance value of the species and the Shannon-Wiener Index of Diversity. In addition the distribution of trees is correlated with certain physico-chemical factors such as air and soil temperature and soil pH. The five most occuring tree species in the area are "Ipil-ipil", "Mahogany", "Gemilina", "Kamunsil" and "Mangga". seedling and sapling of the most leading tree species in the one-hectare plot dominate the area indicating that there is a pattern of replacement and the woody vegetation is regenerating after complete forest clearance due to human activities. Throughout this study, it attempt to integrate the structural characteristics of secondary succession as a way to enhance the ability both to predict and manage successional forest ecosystem due to their increasing importance as timber sources, providers of environmental services and templates for restoration purposes.
Special Problem (Undergraduate, Bachelor of Science in Biology) College of Arts and Sciences, University of the Philippines Visayas, Miagao, Iloilo
Keywords: Secondary Forest -- UP Visayas, Miagao, Iloilo